Acidentes de trabalho graves envolvendo membros superiores notificados em um Centro de Referência em Saúde do Trabalhador - Rosa Júnior, Alberto Pinto da (2018)
INTRODUCTION: Serious occupational accidents occurred even before Industrial Revolution and were intensified after it, becoming a growing target of studies and analysis of many professionals of the area and researchers, since they entail and add up to damages for the worker, his family, the company and the society. By having knowledge of the dynamics of these events and based on the statistics and official notification record sheets, it's possible to develop action plans and goals for its reduction and neutralization, as well as to restructure public policies aimed exclusively at this group of workers, especially those in the informal economy, who have always been on the margins of welfare and social security benefits. OBJECTIVE: Identify serious work accidents involving upper extremity within the area covered by the Reference Center on Occupational Health of Uberlandia-MG. METHODOLOGY: Secondary data were collected from two records: the first one was the compulsory registry sheet of serious accidents and the second was the complementary sheet. RESULTS: A total of 370 registry record sheets was analyzed. Accidents were mainly observed in men, married and with low level of schooling. The construction and carpentry workers were the most affected. The situation characterization evidenced that the accidents occurred at the end of the workday, with peaks at the end of the morning, but more evidenced at the end of the afternoon. There was a reduction in workplace accidents in the period that coincides with school vacation. Most workers did not use personal protective equipment and they had not been trained, and road accidents were not of greater relevance. The Communication of Occupational Accidents occurred in less than a third of the accidents. Saw blades were the main cause of accidents, causing fractures in more than half of the cases and affecting mainly fingers and hands. CONCLUSION: Finger injuries were the accidents that presented greater occurrence, mainly with workers from the informal economy sector. Besides, the lack of technical capacitation and training of these workers is also another factor that must be reviewed to develop and consolidate public policies, aiming to fill this gap that still perpetuates in working environments in Brazil.